Hair cortisol levels and symptoms of anxiety and depression in Chinese adolescents: Comparison between incarcerated and community populations. Issue 1 (16th October 2018) - Xu, Youyun; Li, Jifeng; Xie, Qiaozhen; Deng, Huihua
Abstract: Hair cortisol has been proposed as a temporally integrated measure of systemic cortisol suitable for studies of chronic stress. We compared hair cortisol and depressive and anxiety symptoms between two groups of healthy male adolescents differing in exposure to chronic stress, one attending regular high school ( n = 33) and the other incarcerated for 11–867 days in juvenile detention ( n = 29), and examined the association of hair cortisol and depressive and anxiety symptoms among all adolescents. Hair cortisol was determined by liquid chromatography tandem mass spectrometry, and depressive and anxiety symptoms were measured by the Self‐Rating Depression and Anxiety Scales. Hair samples (1‐cm segments closest to the scalp at the posterior vertex) were collected 2 weeks after psychometric testing. Results revealed that incarcerated adolescents showed significantly more anxiety and depression symptoms, and higher hair cortisol levels than high school adolescents ( p s < .05). The regression results revealed that hair cortisol levels could negatively predict depression symptoms ( p < .05) but could not predict anxiety symptoms ( p > .05) among all adolescents from the two groups. In summary, incarcerated adolescents experienced significantly higher chronic stress than high school adolescents. Hair cortisol showed a negative association with depression symptoms and no association with anxiety symptoms among adolescents with different exposures to chronic stress.